2022
DOI: 10.1111/jbi.14325
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution models and a 60‐year‐old transplant experiment reveal inhibited forest plant range shifts under climate change

Abstract: Aim: Climate change causes species to shift their distributions. Individual species, however, greatly vary in their capacity to track the macroclimatic temperature increase due to differences in demography and dispersal. To better predict range shifts to climate change we need a complementary integration of long-term empirical data and predictive modelling.Location: Belgium and North-West Europe.Taxon: Hyacinthoides non-scripta¸ forest understorey plants. Methods:Complementing species distribution models with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 76 publications
(136 reference statements)
2
12
0
Order By: Relevance
“…For all focal species, the SDMs predicted substantial amounts of suitable habitat beyond their current ranges, indicating that species' potential ranges are considerably larger than their realized ranges. These results corroborate previous modelling and experimental work, suggesting that also non‐climatic factors are important in setting range limits (Louthan et al, 2015; Sanczuk et al, 2022; Shepard et al, 2021). For example, Svenning et al (2008) showed that the ranges of many plants native to European forests are still subject to post‐glacial dispersal limitation (Svenning et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…For all focal species, the SDMs predicted substantial amounts of suitable habitat beyond their current ranges, indicating that species' potential ranges are considerably larger than their realized ranges. These results corroborate previous modelling and experimental work, suggesting that also non‐climatic factors are important in setting range limits (Louthan et al, 2015; Sanczuk et al, 2022; Shepard et al, 2021). For example, Svenning et al (2008) showed that the ranges of many plants native to European forests are still subject to post‐glacial dispersal limitation (Svenning et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Although rarely done, experimentally validating model predictions with field experiments can be particularly informative, as field experiments provide an integrated test of plant and population responses to the macroclimatic, microclimatic and biotic context of the environment (e.g. Greiser et al, 2020; Lee‐Yaw et al, 2016; Sanczuk et al, 2022). In our study, the results observed in the transplant experiment indeed validated the results from the SDMs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations